ANALYSING AND FORECASTING OF DOMESTIC AGRICULTURAL ENTERPRISE’S RESOURCES PROVISION AND UTILIZATION - KULINICH, TETIANA; MARYNCHUK-MIKKELSEN, VIKTORIIA; PANIUS, ULIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers the essence and approbation of the complex methods of analyzing the provision and use of enterprise resources proposed by the authors. The process of such analysis involves consideration of different types of resources: capital, material, labor, financial, information. All these resources are evaluated in terms of security and their use in the enterprise belonging to a particular type of economic activity, taking into account its specifics. For each of the types of resources there is formed a group of indicators that allow to establish the level of provision and use of relevant resources in the enterprise. The selection of indicators is mostly universal, but still partially dependent on the scope of the enterprise. The proposed method is tested on the example of a domestic agricultural enterprise. Therefore, the selection of indicators is modified for this type of economic activity. In the process of analyzing the availability and use of resources in an agricultural enterprise, two key points are provided: the formation of a reference object or base of comparison and conducting a dynamic evaluation. As a basis of comparison (or so-called "reference" object) can be used or conditional object, characterized by industry-average data, estimated by the formed set of indicators (coefficients), or the data of the base competitor for the evaluated enterprise. Depending on the activity specifics and / or on the chosen priorities for resource evaluation, the set of groups of indicators and the list of indicators in groups can be modified. According to the proposed method the evaluation was carried out on the example of one of domestic agricultural enterprises – “Agro-Optima” LLC. Data from the main industry competitor were used as a basis for comparison. A comparison with the average industry object, the indicators of resource use of which are formed and calculated on the basis of Ukrainian State Statistics data is also shown. For a more thorough assessment of resources, the indicators are calculated in the dynamics – for 3 years. The results of the evaluation of given enterprise taking into account the dynamics and average industry values of the selected set of indicators are also used to predict possible achievements and problems that will accompany the future activities of this enterprise, given its resources and their utilization.
Keywords: resources; provision and utilization of resources; analysis and forecasting; agricultural enterprise; method; dynamics; industry-wide comparisons